2022
DOI: 10.1021/acs.jcim.2c00239
|View full text |Cite
|
Sign up to set email alerts
|

CelS-Catalyzed Processive Cellulose Degradation and Cellobiose Extraction for the Production of Bioethanol

Abstract: Bacterial cellulase enzymes are potent candidates for the efficient production of bioethanol, a promising alternative to fossil fuels, from cellulosic biomass. These enzymes catalyze the breakdown of cellulose in plant biomass into simple sugars and then to bioethanol. In the absence of the enzyme, the cellulosic biomass is recalcitrant to decomposition due to fermentationresistant lignin and pectin coatings on the cellulose surface, which make them inaccessible for hydrolysis. Cellobiohydrolase CelS is a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Note that these clusters do not contain information about their location with regard to the catalytic center or cellulose binding domains. The criteria for selecting a preferred cluster that may aid in the adsorption of cellulase onto CNTs were, (i) the elimination of clusters containing multiple carbohydratebinding residues 63 (His68, Glu76, Glu87, Trp184, Asn204, Phe206, Gln247, Asp255, Tyr327, Trp338, Trp340, Tyr431, Gly435, Trp439, Phe442, Asp520, Glu576, Ala577, Arg643, and Trp645), (ii) mostly solvent-exposed, and (iii) more than ∼18 Å away from the active site (Glu87 and Asp255) 64 residues. MD Simulations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Note that these clusters do not contain information about their location with regard to the catalytic center or cellulose binding domains. The criteria for selecting a preferred cluster that may aid in the adsorption of cellulase onto CNTs were, (i) the elimination of clusters containing multiple carbohydratebinding residues 63 (His68, Glu76, Glu87, Trp184, Asn204, Phe206, Gln247, Asp255, Tyr327, Trp338, Trp340, Tyr431, Gly435, Trp439, Phe442, Asp520, Glu576, Ala577, Arg643, and Trp645), (ii) mostly solvent-exposed, and (iii) more than ∼18 Å away from the active site (Glu87 and Asp255) 64 residues. MD Simulations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was shown that the capture of CO 2 by ZIF-8 nanoparticles presupposes dehydration of the atmospheric gas and can be increased by decreasing temperature and/or increasing pressure. Penneru and co-workers employed nonequilibrium steered MD simulation using suitable reaction coordinates to explore the energetics of product expulsion and substrate sliding in the Cellobiohydrolase CelS . The study proposes a molecular mechanism for processive cellulose degradation and cellobiose extraction of relevance for bioethanol production.…”
mentioning
confidence: 99%